GC-HRMS Interactive Heatmap of Confidently Annotated Chemicals - Sunyer Caldú, Adrià (SciLifeLab Serve, 2026)
The INQUIRE project is a large-scale exposomics monitoring campaign of semi-volatile organic compounds (SVOCs) in indoor and outdoor air, sampled across 8 European countries. This interactive heatmap shows confirmed and confidently annotated GC-HRMS chemical features detected across the study, with z-scored intensities and country, indoor/outdoor sampling, confidence level, compound class, and detection frequency annotations. Deployed on SciLifeLab Serve as supplementary material for the manuscript.